Information Overload and Attention Crisis Among Administrative, Technical, and Service Personnel at Cheikh Anta Diop University: A Descriptive Analysis - Sahite GAYE (International Journal of Scientific Research and Innovative Studies, 2025)
In Senegalese public universities, particularly Cheikh Anta Diop University (UCAD) in Dakar, administrative, technical, and service personnel (PATS) face intensified information flows, leading to information overload and an attention crisis. This study, based on a questionnaire administered to 450 PATS with a 72% response rate (N = 325), examines perceptions and management of these flows. Results indicate that over 60% of respondents receive more than 10 messages weekly, with 41% reporting frequent overload. Division heads (66%) and experienced agents face higher exposure. Drawing on psychodynamic theories (Dejours, 2009; Clot, 2010), sociological perspectives (Lipovetsky, 2005), and communication theories (Méadel, 2013; Stiegler, 2010), the study frames these challenges as an institutional attention crisis. The UCAD Strategic Plan (2019–2023) aims to modernize governance through ICT, yet inadequate training and infrastructure exacerbate overload. Recommendations include prioritizing clarity, reducing redundancies, and implementing AI-assisted tools to streamline communication. Keywords: information overload, attention crisis, university organization, digitalization. Received Date: July 19, 2025 Accepted Date: August 11, 2025 Published Date: August 30, 2025 Available Online at <a href="https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/446" target="_blank" rel="noopener" data-saferedirecturl="https://www.google.com/url?q=https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/410&source=gmail&ust=1758913187948000&usg=AOvVaw3DULjvS_QjOrtdyHtr6xsJ">https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/446